2007
DOI: 10.1186/1472-6963-7-186
|View full text |Cite
|
Sign up to set email alerts
|

Public involvement in the priority setting activities of a wait time management initiative: a qualitative case study

Abstract: BackgroundAs no health system can afford to provide all possible services and treatments for the people it serves, each system must set priorities. Priority setting decision makers are increasingly involving the public in policy making. This study focuses on public engagement in a key priority setting context that plagues every health system around the world: wait list management. The purpose of this study is to describe and evaluate priority setting for the Ontario Wait Time Strategy, with special attention t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…Six hundred and twenty studies were excluded from further analysis, because they reported OD projects with consumer participation in other areas than Health Care. Th e remaining 25 studies consisted of 20 studies on OD projects with consumer participation in various areas of Health Care [15,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] and fi ve systematic reviews of 135 [16], 131 [17], 38 [37], 5 [38], and 143 [39] studies, re- spectively. Table 1 describes the study characteristics such as number of participants/projects, type of consumer participation, study design, use of a control group, and area of Health Care of these 25 studies.…”
Section: Resultsmentioning
confidence: 99%
“…Six hundred and twenty studies were excluded from further analysis, because they reported OD projects with consumer participation in other areas than Health Care. Th e remaining 25 studies consisted of 20 studies on OD projects with consumer participation in various areas of Health Care [15,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] and fi ve systematic reviews of 135 [16], 131 [17], 38 [37], 5 [38], and 143 [39] studies, re- spectively. Table 1 describes the study characteristics such as number of participants/projects, type of consumer participation, study design, use of a control group, and area of Health Care of these 25 studies.…”
Section: Resultsmentioning
confidence: 99%
“…This is especially true in the fields of cancer, joint replacement surgeries (arthroplasties), sight restoration, cardiac problems and diagnostic imaging among others (Bruni et al ., 2007) 44. Briggs et al ., (2011)45 reviewed the effect of active management of surgical waiting lists in a urological service in Australia, which resulted in a significant reduction in the surgical waiting times for semi-urgent and non-urgent patients from 248-180 days in the 10-month period of the review.…”
Section: Discussionmentioning
confidence: 99%
“…Previously we conducted a qualitative case study to describe and evaluate the priority setting activities of the OWTS, with particular attention to public engagement [22]. This previous study was guided by an explicit conceptual framework -'accountability for reasonableness' [23] is a conceptual framework for legitimate and fair priority setting.…”
Section: The Ontario Wait Time Strategymentioning
confidence: 99%
“…An interview guide was developed based on previous research [22,[29][30][31] and was revised during data collection in order to pursue emerging findings. For example, participants unexpectedly discussed distrust with the OWTS information.…”
Section: Data Collectionmentioning
confidence: 99%